MULTIDIMENSIONAL INDICATORS OF SPORTING POTENTIAL OF BRAZILIAN TRAMPOLINE GYMNASTS - Kerly Priscila Jesus de Oliveira; Paulo Carrara; Emerson Filipino Coelho; Renato Melo Ferreira; Katya Mourthé; Newton Santos Vianna Júnior; Francisco Zacaron Werneck (Journal of Physical Education)
ABSTRACT The scientific evidence on the profile of trampoline gymnastic athletes is scarce. Considering that the individual trampoline is an Olympic sport, it is important to investigate the characteristics of these athletes in Brazil. The aim of this study was to evaluate anthropometric, physical-motor, maturational, socio-environmental indicators and the sporting potential of Brazilian trampoline gymnasts, investigating differences between age categories. There were 147 athletes participating who competed in the State and Brazilian Championship of Trampoline Gymnastics by Age Group in 2017-2018. A multidimensional battery of tests was carried out, comparing the indicators collected between the categories 9 to 10 years, 11 to 12 years, 13 to 14 years, 15 to 16 years and 17 years or older. The coaches (n = 20) assessed the sporting potential of their gymnasts, in relation to the expectation of success in the future. The results showed statistically significant differences in body size and composition, somatotype, handgrip strength, countermovement jump, flexibility and sporting potential among athletes of different age categories, in both sexes. In addition, 30% of gymnasts showed high sporting potential, according to the perspectives of the coaches. It is concluded that the multidimensional indicators related to the sporting potential of Brazilian trampoline gymnasts vary according to the age category. This study is a pioneer in characterizing the profile of the elite Brazilian trampoline gymnast, using a dynamic approach related to the sporting talent.